Paraneoplastic Pemphigus Revealed by Anti-programmed Death-1 Pembrolizumab Therapy for Cutaneous Squamous Cell Carcinoma Complicating Hidradenitis Suppurativa - Yatim, Ahmad; Bohelay, Gérôme; Grootenboer-Mignot, Sabine; Prost-Squarcioni, Catherine; Alexandre, Marina; Le Roux-Villet, Christelle; Martin, Antoine; Maubec, Eve; Caux, Frédéric (Frontiers in Medicine, 2019)
A 64-year-old patient developed a widespread autoimmune mucocutaneous blistering disease 3 weeks after the initiation of the anti-programmed death-1 (anti-PD-1) pembrolizumab therapy administered for a locally advanced cutaneous squamous cell carcinoma (SCC) of the buttocks arising from hidradenitis suppurativa. A diagnosis of paraneoplastic pemphigus (PNP) was made based on the presence of a suprabasal acantholysis associated with intercellular deposits of immunoglobulin G and C3 on basement membrane zone. Analysis of the patient's sera was positive on monkey bladder and detected circulating antibodies against desmoglein 3 and desmoplakin I prior to the initiation of pembrolizumab. At that time, the patient had few localized blisters limited to the peri-tumoral skin of the buttocks with acantholysis but without in vivo immune deposits. Pembrolizumab therapy was discontinued and a complete remission of PNP was obtained using oral steroids. Reintroduction of pembrolizumab resulted in flare of PNP. Given the close temporal relation between pembrolizumab initiation and the subsequent clinical expression of a widespread PNP, the patient was diagnosed with pre-existing subclinical PNP exacerbated by PD-1 inhibitor. The extreme rarity of PNP in the setting of cutaneous SCC and the effects of challenge, dechallenge, and rechallenge of pembrolizumab argue in favor of a checkpoint inhibitor related adverse effect. Our case is the first PNP associated with anti-PD-1 therapy and serological follow-up suggest that one infusion of pembrolizumab is sufficient to allow clinical expression of underlying pemphigus auto-immunity.